2014
DOI: 10.1039/c4dt00430b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and phonon transport in Sb-doped Ti0.1Zr0.9Ni1+xSn0.975Sb0.025 nanocomposites

Abstract: The thermoelectric behavior of n-type Sb-doped half-Heusler (HH)-full-Heusler (FH) nanocomposites with general composition Ti(0.1)Zr(0.9)Ni(1+x)Sn(0.975)Sb(0.025) (x = 0, 0.02, 0.04, 0.1) was investigated in the temperature range from 300 to 775 K. Samples used for structural characterization and transport measurements were obtained through the solid-state reaction of high purity elements at 950 °C and densification of the resulting polycrystalline powders using a uniaxial hot press. X-ray diffraction study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…In our earlier work, [23] [30] we demonstrated that the substitution of a Figure 3E. In our earlier work, [23] [30] we demonstrated that the substitution of a Figure 3E.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…In our earlier work, [23] [30] we demonstrated that the substitution of a Figure 3E. In our earlier work, [23] [30] we demonstrated that the substitution of a Figure 3E.…”
Section: Resultsmentioning
confidence: 53%
“…This can be achieved by increasing mass fluctuation or point defects in the sample [23][24][25][26][27] . In our previous research, we focused on coherently embedding full-Heusler (FH) phases as nanostructures in bulk HH alloys [23][24][25][29][30][31] . In our previous research, we focused on coherently embedding full-Heusler (FH) phases as nanostructures in bulk HH alloys [23][24][25][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] The XNiSn solid solution is the most extensively studied n-type HH system. 3,4,[10][11][12][13][14][15][16][17] Much of the existing literature focuses on the thermoelectric characterization of n-type XNiSn and p-type XCoSb solid solutions, whereas studies on p-type XNiSn-based HHs are far fewer in number. The most promising p-type HHs are found in the XCoSb system (X ¼ Ti, Zr, Hf).…”
mentioning
confidence: 99%